KORELASI ANTARA EFIKASI DIRI DENGAN PRESTASI BELAJAR MAHASISWA PENDIDIKAN MATEMATIKA PADA MATERI GEOMETRI - Nilza Humaira Salsabila; Dwi Novitasari; Nyoman Sridana (Edutainment, 2021)
This study aims to determine the correlation between self-efficacy and student achievement in mathematics education on Geometry. The type of research conducted in this research is correlational research with a quantitative approach. The subjects of this study were 21 semester 5 mathematics education students who took the Spatial Analytical Geometry course. The data collection technique used is a questionnaire technique to obtain self-efficacy data and documentation techniques to obtain student achievement data on the topic of Spatial Analytical Geometry. The data analysis technique used to test the research hypothesis is using a simple correlation analysis technique. The results of the research conducted showed that there was a significant correlation between self-efficacy and learning achievement of mathematics education students on Geometry topic with the value of Sig. (2-tailed) of 0.014 < 0.05. In addition, there is a positive relationship between student self-efficacy and learning achievement in geometry. This indicates that the more students' self-efficacy increases, the learning achievement will also increase.